English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

step by step!

2007-05-21 16:07:41 · 4 answers · asked by Anonymous in Science & Mathematics Mathematics

4 answers

You can use the quadratic equation and plug the numbers in.

2007-05-21 16:10:47 · answer #1 · answered by Anonymous · 0 0

use the quadratic formula
(-(b^2) +/-sqrt(b^2 - 4*a*c))/a^2
where
a = the coefficient of the second degree term
b = the coefficient of the first degree term
c = the coefficient of the zero degree term

(-(-6^2) +/-sqrt((-6)^2 - 4*(2)*(-55)))/(2)^2
(-36 +/- sqrt(476))/4
answers: (-18+sqrt(119))/2,(-18-sqrt(119))/2

2007-05-21 23:13:52 · answer #2 · answered by Anonymous · 0 0

Do you know the quadratic equation? It is the key to solving this problem. Search "quadratic equation" on google or yahoo.

2007-05-21 23:12:52 · answer #3 · answered by Colin 2 · 0 0

x = [6 ± √(36 + 440)] / 4
x = [6 ± √(476)] / 4
x = [6 ± (21.8)] / 4
x = 6.95 , x = - 3.95

2007-05-22 02:34:52 · answer #4 · answered by Como 7 · 0 0

fedest.com, questions and answers